Annual abstract of statistics, 1961 - Nigeria. Federal Office of Statistics (Lagos: Federal Office of Statistics, 1961)
This annual abstract of statistics, 1961 edition covers: area and climate; population and migration; social conditions employment; education; production; transport and communication; external trade; balance of trade; prices; national accounts; public finance; banking and insurance and general elections.
lje 14/03/2019
Ref.
Keywords: Economic conditions--Statistics; Industrial statistics; Population--Statistics; Nigeria